Vibrational spectroscopy for tissue analysis - Rehman, Ihtesham ur (Series in medical physics and biomedical engineering, 2013)
"This book presents a variety of vibrational spectroscopic techniques, focusing on Raman and Fourier transform infrared (FTIR) spectroscopy and their use in noninvasive optical tissue diagnosis. It covers the most recent research in this area to create a unique database of different chemical bands and their assignments of spectral bands. The text explores the spectroscopic investigation of different tissues and samples, including breast tissue, lung tissue, and brain tissue. Based on their years of experience with various applications, the authors provide definitions of peak frequencies as well as other aspects of spectroscopy that could be helpful to a wide range of scientists"--Provided by publisher.